Linguistic Landscape: Reports on immigrant language at Asian-Australian community - Fadhlur Rahman; Muntasir Muntasir (EduLite: Journal of English Education, Literature and Culture, 2022)
Studies in linguistic landscape (LL) have been emerged as one of the growing topics in the societal multilingualism. Linguistic landscape transpires as a significant element to study linguistic contacts in multilingual settings. Despite the fact that Australia has been acknowledged as one of the multilingual hotspots, a study in linguistic landscape received scant attention among scholars. In enhancing a broad appreciation of the linguistic diversity at the multilingual society like Australia, thus, the centrality of this article is to report significant component of rich linguistic scenes at Springvale-Greater Dandenong, Victoria. The sources of data were derived from visual data, and further will be intertwined with the consensus data. Taken together, the twofold data presented in this article have revealed that the LL studies emerge as an important element to contribute to the richness of multi-ethnic representation in multilingual societies. The result showed that English translation is mostly found in the terrestrial signage, this appearance denotes the significance of English language as an official signage or a lingua franca for the community rather than a bilingual outward appearance. Despite English language has been identified as the dominant language representation though the signage, there are a buoyance of minority languages representation in the city of Springvale’s LL.